2020
DOI: 10.1016/j.jsps.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms of Chinese Herbal Medicine that implicated in the treatment of COVID-19 related renal injury

Abstract: Highlight: It was proven that renal injury in Corona Virus Disease 2019 (COVID-19) patients has been a real concern. There are three possible mechanisms of renal injury in COVID-19 infection: direct viral mediated, prolonged cytokine storm mediated, and drug-induced renal injury. There is no targeted drug therapy in the treatment of renal injury, while Chinese Herbal Medicine can be a potential solution. Huang Qi, Fu Ling, Di Huang, Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…He et al collected prescriptions for the treatment of renal injury in CHM clinical reports from databases such as the China National Knowledge Infrastructure (CNKI), VIP, and Wanfang. Frequency statistics were performed on herbs among all the prescriptions recorded, and the association rules analysis showed that the core herbs included Huang Qi (Radix astragali), Fu Ling (Poria), Bai Zhu (Rhizoma atractylodis macrocephalae), Shan Yao (Rhizoma dioscoreae), and Di Huang (Radix rehmanniae) (15), which was generally consistent with the clinical medications of this study. Huang Qi, Fu Ling, Bai Zhu, and Shan Yao strengthen the spleen, benefit Qi, and remove dampness.…”
Section: Discussionsupporting
confidence: 77%
“…He et al collected prescriptions for the treatment of renal injury in CHM clinical reports from databases such as the China National Knowledge Infrastructure (CNKI), VIP, and Wanfang. Frequency statistics were performed on herbs among all the prescriptions recorded, and the association rules analysis showed that the core herbs included Huang Qi (Radix astragali), Fu Ling (Poria), Bai Zhu (Rhizoma atractylodis macrocephalae), Shan Yao (Rhizoma dioscoreae), and Di Huang (Radix rehmanniae) (15), which was generally consistent with the clinical medications of this study. Huang Qi, Fu Ling, Bai Zhu, and Shan Yao strengthen the spleen, benefit Qi, and remove dampness.…”
Section: Discussionsupporting
confidence: 77%
“…3 , the proteins in the center of the PPI are PTGS2, IL6, TNF, MAPK14, and so on, which may play an important role in the treatment of COVID-19 with TQG. PTGS2, encoding COX2, plays an important role in SARS-CoV infections and SARS-CoV N protein causes lung inflammation by activating COX2 and stimulating multiple COX2 inflammatory cascades ( Elkahloun and Saavedra, 2020 ; He et al., 2020 ). IL-6 plays an important role in the immunopathogenesis of COVID-19 and is supported by data from a range of studies reporting increased serum concentrations of this cytokine, foremost in the severe cases ( Nasonov and Samsonov, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although a great quantity of review articles have been published on the topic of TCM in COVID-19 13 , 14 , 19 , 23 , 25 , 35 , 71 , 87 , 168 , 171 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , our work offers something unique. 1) To our knowledge, this is the first review of TCM on COVID-19 that integrates evidence-based scientific findings from bedside to bench with the most comprehensive and updated literatures.…”
Section: Discussionmentioning
confidence: 99%